Pengaruh Gaya Hidup Dan Etnosentrisme Konsumen Terhadap Keputusan Pembelian Dengan Niat Beli Sebagai Mediator - Izza Nafila Nasution; Intan Tri Annisa (Jurnal Mirai Management, 2025)
This study aims to determine the effect of lifestyle, consumer ethnocentrism on purchase decision and purchase intention as mediator on consumer local cosmetics in Jabodetabek. The sample in this study was 115 consumers of local cosmetics in Jabodetabek who had bought and used local cosmetics. The sampling technique used is purposive sampling. Data was collected using a survey method with an instrument in the form of a questionnaire. The data analysis method used is the SPSS method and Partial Last Square Structural Equation Modeling (PLS- SEM). The results showed that (1) lifestyle had no effect on purchase decision (2) consumer ethnocentrism had a positive and significant effect on purchase decision (3) lifestyle had a positive and significant effect on purchase intention (4) .consumer ethnocentrism had a positive and significant effect on purchase intention (5) purchase intention has a positive and significant effect on purchase decision (6) purchase intention can mediate the effect of lifestyle on purchase decision (7) purchase intention can mediate the effect of consumer ethnocentrism on purchase decision. Keywords: Lifestyle, consumer ethnocentrism, purchase intention, purchase decision.